Being an educator for developing age subjects, having experienced their mother's femicide. Constitutive elements for a pedagogy of bereavement - Maria Rita Mancaniello (University of Bologna, 2022)
The phenomenon of femicide is a social tragedy, keeping on being perpetrated across time. Its consequences are deeply traumatic for children and adolescents, becoming motherless, by their father or by their agent of fatherly care. It represents a serious trauma, still needing to be adequately addressed, by the different human sciences and, especially, involving pedagogy in a careful reflection, in order to facilitate full development processes for a subject in a childhood and adolescence age. The reference, here, is to a pedagogy of bereavement, grounded in attentive categories of analysis and in educative methodologies, able to strengthen life value and to activate an existential planning. It should act in the purpose of allowing each orphaned subject - due to femicide -being capable of building his/her own meaningful future, worthy to be wished and towards which addressing the own search of meaning.